Moone boy. The complete series. [videorecording (DVD)] - McDonald, Peter, 1972-; O'Dowd, Chris, 1980-; Rawle, David; O'Kane, Deirdre (BBC US / Canada, 2016)
The hilarious, semi-autobiographical tale of Martin Moone, the youngest boy in a loud, large Irish family, and his imaginary friend Sean Murphy. Between Martin's unique view on life and Sean's not always helpful advice, the pair find themselves thrown into one ridiculous scheme after another. Revel in this hilarious, award-winning hit show, now together in one complete collection for the first time!